A chaotic image encryption algorithm based on sliding window and pseudo-random stack shuffling - Cao, Pengfei; Teng, Lin (Nonlinear dynamics, 2024)
This paper introduces a new one-dimensional chaotic system, which can be considered as an improvement upon the Bernoulli map. The Quadratic Bernoulli Chaotic System (QBCS) is introduced by replacing the linear segment of the Bernoulli map's two segments with quadratic nonlinearity. Subsequently, an image encryption algorithm is proposed, utilizing a sliding window mechanism and dynamic stack sequences. Initially, the position of the initial window is determined, and to ensure the traversal of the window, the initial window position is set to the top-left corner of the original image. Subsequently, the step size for window movement is determined, and chaotic sequences generated by QBCS are used to scramble the contents selected by each window. Moreover, on the basis of the standard index scrambling concept, a dynamic stack traversal method is employed, wherein the behavior of elements entering and exiting the stack is determined according to the chaotic sequences generated by QBCS, effectively expanding the value space of the chaotic index sequence. Furthermore, combined with the chaotic sequences generated by QBCS, a diffusion process using distribution dilution is applied to the contents within each window. Experimental simulations and performance analysis demonstrate the algorithm's robust security.